Analisis Dugaan Praktik Predatory Pricing dan Penyalahgunaan Posisi Dominan dalam Industri E-commerce - Akhmad Farhan Nazhari; Naufal Irkham (Jurnal Persaingan Usaha, 2023)
Abstract Digital trade activities in the form of e-commerce inseparable from the Covid-19 pandemic which has increased the number of users of e-commerce platforms. Unfortunately, this also poses challenges related to business competition, which are marked by some allegations regarding predatory pricing practices and/or abuse of dominant market position, as well as challenges in supervising business competition by KPPU. Therefore, the author will examine these challenges based on Law No. 5 of 1999 using normative juridical research method, as well as the hope that KPPU as quasi-institutional can make guidelines for supervising business competition in the market concerned of e-commerce. Keywords: e-commerce; dominant position; price discrimination; supervision.